THE IMPACT OF TECHNOLOGY ON LEARNING ENGLISH - Norbutayev Xushnud Eshnazar ugli (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In the modern era, technology has significantly transformed the process of learning English. Digital tools, online platforms, and mobile applications have made language learning more accessible, interactive, and effective. This article explores the role of technology in improving language skills, enhancing learner motivation, and providing flexible learning opportunities. In addition, it examines modern approaches such as blended learning, artificial intelligence, and gamification in language education. The article also discusses both the advantages and potential challenges of using technology in English language education.